(untitled) (KYAMC Journal, 2022)
Background: Public awareness-creating activities have been taking place to promote blood donation but the units still do not match the yearly demands for blood. Prevalence of transfusion transmissible infection also happens to be a problem. Objective: To study the difference of ratio in between male and female donors as well as the trend of transfusion transmissible diseases. Materials and Methods: The present study has 56,557 blood donors over fourteen long years (2008 – 2021) by the Department of Transfusion Medicine at Khwaja Yunus Ali Medical College & Hospital (KYAMCH). Result: The donor medical assessment was passed by 56,557 people over 14 years; the number of females were 4,661 in compare to 51,896 males. Regarding the results of TTI screening, it is to be noted that only 688 positive cases were found among 56,557 people – implying only about 1.2% of the potential donor population being rejected. Conclusion: The data analysis has shed some light on the demography of donors and also Transfusion Transmissible Infections (TTIs) trends over the study period. KYAMC Journal Vol. 13, No. 02, July 2022: 72-75